New Multicomponent Forms of the Antiretroviral Nevirapine with Improved Dissolution Performance - Costa, Rogeria Nunes (2020)
In the pharmaceutical area, some drugs exhibit physicochemical properties that adversely affect the formulation processes for bioavailability and effectiveness. Nevirapine (NVP) is an antiretroviral drug that presents low aqueous solubility, which directly impacts its bioavailability. Among all possible modifications, multicomponent crystals, such as cocrystals and eutectic compositions, have been successfully used to improve the solubility of drugs. In this work, the propensity of the formation of multicomponent systems of NVP with seven possible coformers were predicted and tested: salicylic acid (SA), 3-hydroxybenzoic acid (3HBZC), 4-hydroxybenzoic acid (4HBZC), saccharin (SAC), theophylline (THEO), caffeine (CAF), and urea (URE). Results indicate that NVP-SA, NVP-SAC, NVP-3HBZC, and NVP-4HBZC are cocrystals, whereas NVP-THEO and NVP-CAF are eutectic materials, and NVP-URE is a solid physical mixture. A temperature-dependent disorder behavior was identified for NVP-SA cocrystal. Dissolution studies for the eutectic materials are reported, evidencing that these materials exhibit a significant increase in NVP dissolution kinetics.